GABAB receptors negatively modulate excitatory plasticity at the mossy fiber synapse onto parvalbumin-expressing basket and axo-axonic cells in the dentate gyrus - Loureiro, Rita M.; Booker, Sam A.; Kulik, Akos; Vida, Imre (Frontiers in Synaptic Neuroscience, 2025)
IntroductionGABAB receptors (GABABRs) are important modulators of neuronal excitability, synaptic transmission and plasticity in principal cells (PCs). While at the cellular level they can inhibit synaptic transmission directly, at the network level, due to a net disinhibitory effect, they promote plasticity in PCs. However, their effect on plasticity in GABAergic interneurons (INs) is less well-understood.MethodsIn this study, we have combined quantitative immunoelectron microscopy and ex vivo whole-cell recordings to investigate the surface expression of GABABRs and their modulation of synaptic plasticity at mossy fiber (MF) inputs onto parvalbumin-expressing interneurons (PV-INs) in the rat dentate gyrus (DG).ResultsImmunoelectron microscopy confirmed the expression of the GABABRs and their effector channel Kir3.1 on PV-IN dendritic shafts. Theta-burst extracellular stimulation of MFs resulted in robust long-term potentiation (LTP) in basket cells (BCs) and axo-axonic cells (AACs), the two main types of DG PV-INs. LTP in both types was strongly reduced, but not abolished, by the GABABR agonist baclofen.Discussion/ConclusionFinally, pre-application of SCH-23390, a blocker of Kir3 channels, occluded the inhibitory effect of baclofen on LTP. These results demonstrate that postsynaptic GABABRs negatively regulate synaptic plasticity at MF synapses onto DG perisomatic-inhibitory PV-INs via Kir3 channels.